Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to prove the following (which I think is true!): if $f:[0,1]\rightarrow \mathbb{R}$ is twice continuously differentiable and $f(0)=0=f(1)$, then for every $x \in (0,1)$ there exists $\xi \in (0,1)$ such that $f(x) = \frac{1}{2}x(x-1) f''(\xi)$. Does anyone have a neat proof of this?

My idea, following the proof of the ordinary Taylor expansion, is to use the mean value theorem with some appropriately chosen function. For fixed $x$ we would like to have $g$ such that, say, $$ g'(y) = \frac{1}{2}x(x-1)f''(y)-f(x), $$ and prove that $g'(y)=0$ for some $y$. It would be sufficient, by the mean value theorem, that $g(0)=0=g(1)$. The formula gives $$ g(y) =\frac{1}{2}x(x-1)f'(y)-f(x)y + C_1, $$ which will not give $g(0)=0=g(1)$ for any $C_1$. Instead if we choose $$ g'(y) = \left( \frac{1}{2}x(x-1)f''(y)-f(x) \right) (y-a), $$ we get $$ g(y) = \frac{1}{2}x(x-1)\left( f'(y)(y-a)-f(y) \right) -f(x)\left( \frac{y^2}{2} -ay \right) + b. $$ We choose $a$ and $b$ to give us $g(0)=0=g(1)$. Indeed, we have (recalling that $f(0)=0=f(1)$), $$ \begin{pmatrix} -\frac{1}{2}x(x-1) f'(0) &1 \\ -\frac{1}{2}x(x-1) f'(1)+f(x) &1 \end{pmatrix} \begin{pmatrix} a \\ b \end{pmatrix}= \begin{pmatrix} 0 \\ -\frac{1}{2}x(x-1) f'(1) + \frac{1}{2}f(x) \end{pmatrix}. $$ If the matrix here is not invertible, we have $$ -\frac{1}{2}x(x-1) f'(0) = -\frac{1}{2}x(x-1) f'(1) + f(x) $$ $$ \implies f(x) = \frac{1}{2}x(x-1) ( f'(1)-f'(0) ) = \frac{1}{2}x(x-1) f''(\xi) $$ by the MVT applied to $f'$ on $[0,1]$. If the matrix is invertible we can solve for $a$ and $b$. Then $g(0)=0=g(1)$ and so $g'(y)=0$ somewhere in $(0,1)$. Then if $y \neq a$, $$ \left( \frac{1}{2}x(x-1)f''(y)-f(x) \right)=0, $$ which is what we want.

But, ugh. Not a nice proof. And we haven't shown that $y \neq a$....!

share|cite|improve this question
up vote 0 down vote accepted

My friend has answered this nicely. The proof is along the same lines. Define $$ g(y) = f(y) - \frac{y(y-1)}{2}\frac{2}{x(x-1)}f(x). $$ This function is designed so that $g(0)=g(x)=g(1)=0$, where we use the fact that $f(0)=f(1)=0$. So there exists, by the Mean Value Theorem, points $c_1 \in (0,x)$ and $c_2 \in (x,1)$ such that $g'(c_1)=g'(c_2)=0$. Next, by the Mean Value Theorem again, there exists $c_3 \in (c_1, c_2)$ such that $g''(c_3)=0$. But $$ g''(y) = f''(y) -\frac{2}{x(x-1)}f(x) \implies f(x) = \frac{x(x-1)}{2} f''(c_3). $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.